Semantic Contrastive Analysis of the Adjectives Usui and Tipis in Japanese and Indonesian - Fajriati, Tiara Kurnia; Sutedi, Dedi; Rasiban, Linna Meilia (KIRYOKU, 2025)
This study compares the semantic similarities and differences between the Japanese adjective usui and the Indonesian adjective tipis. Using a qualitative method based on Koyanagi’s linguistic phenomena, data were collected from a Japanese language corpus such as nlb.ninjal.ac.jp from 1985 to 2005 and news articles in both Japanese and Indonesian (asahi.com, nhk.co.jp, jawapos.com, cnbcindonesia.com, antaranews.com and tribunnews.com from 2015 to 2024). The findings reveal seven shared meanings: (1) a short distance between two surfaces, (2) thin layers, (3) low gas density, (4) sparse hair or fur, (5) minimal impact or benefit, (6) subtle emotional expression, and (7) weak belief or confidence. Differences in semantic scope were also identified. Usui includes additional meanings such as (1) pale in color, (2) diluted, and (3) bland in taste or senses that not present in tipis. Conversely, tipis also conveys the meaning of (1) being easily irritated, which is not found in usui. Additionally, the study identifies instances of icchi, ketsujou, and shinki. These findings offer valuable insights that may benefit beginner to semi-advanced Japanese language learners and Japanese language teaching, particularly in the field of language education and semantic understanding.